Aspek Hukum Layanan Sertifikat Tanah Elektronik - Dwi Wulan Titik Andari; Dian Aries Mujiburohman (Al-Adl : Jurnal Hukum, 2023)
Modernization of electronic-based land services is a means of increasing indicators of ease of public service to the community. This is implemented by optimizing the use of information and communication technology. This article discusses the legal pitfalls of regulating electronic certificates and the prerequisites for implementing electronic certificates. From this legal blemish, there is formal legal disregard for the fundamental agrarian Law (UUPA) because it is not a source of reference in regulating electronic certificates and electronic land registration, and there are regulatory inconsistencies in the UUPA in substance. On the other hand, the regulation regarding analog land registration (PP No. 24 of 1997) and electronic land registration (PP No. 18 of 2021) raises the interpretation that there are two land registration systems, namely analog and electronic. PP No. 24 of 1997 was revised by issuing new arrangements that included other materials such as management rights, land rights and flats, as in PP no. 18 of 2021. Then, to carry out electronic land registration, at least three conditions must be met, namely validation of land data, electronic documents, and security of land data